Prevalence of Dysfunctional Breathing in Subjects Undergoing Maintenance Dialysis: A Cross-sectional Study - Neha D Bora; Abhishek S Mishra; Preeti S Ganachari; Santosh P Dobhal (Indian Journal of Respiratory Care)
Aim: To determine the prevalence of dysfunctional breathing (DB) in subjects undergoing maintenance dialysis. Background: DB involves abnormal breathing patterns either without organic disease or secondary to cardiopulmonary/neurological conditions like asthma or heart failure. Indicators include asynchronous thoracic and abdominal movements, upper thoracic breathing, frequent sighs, mouth breathing, and excessive use of accessory respiratory muscles. DB can be assessed using the Nijmegen Questionnaire (NQ) and the Self-evaluation of Breathing Questionnaire (SEBQ). The NQ, with a sensitivity of 91% and specificity of 95%, considers a score above 23 indicative of DB. The SEBQ, with an intraclass correlation coefficient of 0.89, uses a cutoff score of 11 for DB. Additionally, the Manual Assessment of Respiratory Motion (MARM) helps assess DB through physical examination. Materials and methods: The study enrolled 69 participants aged 18–60 who had undergone more than three dialysis cycles. Exclusions included chronic respiratory disease, recent abdominal surgeries, and smoking. Participants completed the NQ and SEBQ, followed by an MARM physical assessment. Results: The average age of participants was 41.8 ± 10.9 years. Of the 69 subjects, 21 scored above 23 on the NQ, indicating DB in 30.43% of the sample. On the SEBQ, 66 subjects scored above 11, indicating DB in 95.65%. MARM helped identify abnormal breathing patterns and asymmetry. Conclusion: Using the NQ and SEBQ, the prevalence of DB in subjects undergoing dialysis was found to be 30.43 and 95.65%, respectively.